Performance analysis of proactive routing protocol based on different network load in Mobile Ad-hoc Network (MANET) [Analiza wydajnoci proaktywnego protokou routingu opartego na roznym obciazeniu sieci w mobilnej sieci Ad-hoc (MANET)] - Che Zalina Zulkifli (Tanjung Malim, 2023)
Performance analysis of proactive routing protocol based on different network load in Mobile Ad-hoc Network (MANET) [Analiza wydajnoci proaktywnego protokou routingu opartego na roznym obciazeniu sieci w mobilnej sieci Ad-hoc (MANET)] by Che Zalina Zulkifli